Inventarisasi Dan Formulasi Tanaman Pestisida Nabati Pada Petani Di Sumatera Barat - Yuliartati Yuliartati; Sri Zulyanti Mardhiah; Arian Dodi; Syukri Arief; May Efdi (Jurnal Penelitian Pertanian Terapan, 2024)
This study aims to inventory the plants used by farmers in West Sumatra to make vegetable pesticide ingredients and determine their effectiveness and to formulate botanical pesticides based on their effectiveness in killing insects. Data collection was carried out by direct interviews with farmers. Testing the active substance content of vegetable pesticides is carried out by means of a phytochemical test in the laboratory. The effectiveness of the plant extracts from the inventory was tested in the laboratory. Testing the effectiveness of botanical pesticide formulations is carried out in the field. Formulation effectiveness data were observed qualitatively by farmer groups from the number of leaf vegetables eaten by caterpillars or insects for approximately 2 weeks. There were 44 (forty four) species of plants used by farmers as ingredients for making vegetable pesticides, and 20 (twenty) species of phytochemical tests were carried out, followed by 17 (seventeen) species of effectiveness tests. Formulas for vegetable pesticides are made based on the results of laboratory extract effectiveness tests. The results of the study showed that plants that were effective as ingredients for vegetable pesticides were surian, neem, karakok, citronella which were made with the following formulations: Formula 1 (Surian and Karakok), Formula 2 (Surian, Mindi, Karakok), Formula 3 (Mindi and Karakok) , and Formula 4 (Surian, Mindi, Karakok, Lemongrass Wangi). The results of the effectiveness test of the botanical pesticide formulas in the field showed that the F2 and 4 formulas were more effective than the F1 and F3.